HISTÓRIA EVOLUTIVA DA BACIA DO PRATA: UMA ABORDAGEM NA CONSERVAÇÃO DE ESPÉCIES ARBÓREAS - FARIAS, Ivan Justino; PONTARA, Vanessa; CURIEL, Matheus Henrique; GUIMARÃES, Felipe da Silva; SANTOS, Elizandra Lima dos; BUENO, Marcelo Leandro (ANAIS DO ENIC, 2022)
-